2006
DOI: 10.1300/j181v03n03_02
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SARS Visiting Restrictions on Relatives of Long-Term Care Residents

Abstract: During the Severe Acute Respiratory Syndrome (SARS) outbreaks in Toronto, Canada, families of residents of long-term care settings were significantly restricted in their visiting. Social workers and other staff had to be creative in order to support families, to keep them informed and involved. The research described here was conducted in order to understand families' experiences and evaluate the effectiveness of social work interventions during the SARS visiting restrictions. Focus groups were conducted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 9 publications
2
23
0
Order By: Relevance
“…These findings are consistent with previous studies who found that isolated older adults are at higher risk of depression and anxiety. 8,20 Other studies found that social isolation of older adults is also associated with cardiovascular and cognitive decline. 9,10,21 Adverse effects on health and well-being seem to be a prevalent argument in the debate on discarding visiting restrictions.…”
Section: Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with previous studies who found that isolated older adults are at higher risk of depression and anxiety. 8,20 Other studies found that social isolation of older adults is also associated with cardiovascular and cognitive decline. 9,10,21 Adverse effects on health and well-being seem to be a prevalent argument in the debate on discarding visiting restrictions.…”
Section: Key Findingsmentioning
confidence: 99%
“…5 Isolating policies are widely recommended to prevent COVID-19 contagion 6,7 ; however, consequential detrimental effects of isolating nursing home residents on quality of life are known from the 2003 SARS outbreak. 8 A qualitative study of McCleary 8 found that as a result of nursing home visiting restrictions during the 2003 SARS outbreak, both nursing home residents and their relatives experienced a negative impact on their physical and emotional well-being. Previous studies have also found that chronic isolation of older adults was associated with cognitive decline and anxiety.…”
mentioning
confidence: 99%
“… 25 , 26 Previous research on visitor bans as a consequence of the SARS outbreak revealed a range of negative effects on the physical and mental health of family caregivers. 27 In addition to missing the company of the person with dementia, family caregivers reported experiencing fear, worry, loss of control, frustration, and guilt. 27 …”
Section: Introductionmentioning
confidence: 99%
“…Provincial funding organizations may need to proactively increase staff levels or repurpose staff, such as social workers and recreational therapists, to support communication, psychosocial, education, and infection control needs of residents and families during a pandemic. ( 26 , 27 ) Education and reminders must be provided for families who enter LTC homes on self-monitoring a wide range of possible illness presentations, physical distancing, isolation before, between and after visits, and infection control practices such as hand hygiene, respiratory etiquette, and PPE donning and doffing. Consideration should be given to allow designated family members to co-habit on site for patients/residents who are most vulnerable to negative physical and psychosocial outcomes from visitation restrictions, such as those with higher physical and psychosocial support needs and those who cannot use alternate forms of communication.…”
Section: Introductionmentioning
confidence: 99%